Characterizations of a helix in the pseudo - Galilean space G13 - Külahci, Mihriban (My University, 2010)
In this manuscript, we obtained some characterizations for a helix in the pseudo-Galilean space G G13. © 2010 Academic Journals.
Keywords: Helix; Position vector; Pseudo-galilean space